HISTORY MEETS FICTION IN DOCTOR WHO, 'THE FIRES OF POMPEII': A BBC RECEPTION OF ANCIENT ROME ON SCREEN AND ONLINE. - Hobden, Fiona (Greece & Rome, 2009)
The article presents the analysis of "The Fires of Pompeii," the second episode in the fourth season of British Broadcasting Corp.'s (BBC's) science-fiction drama "Doctor Who." It notes that the episode offers an engaging contemporary reception of the Roman world on television (TV). It helps flourishing discussion of antiquity in popular culture. It requires a recognizable past and considers believability of the family necessary to its brief.